CONCURSUS REALIS PEGAWAI PUSAT KOPERASI VETERAN REPUBLIK INDONESIA (STUDI PUTUSAN NO. 231/PID.B/2021/PN.GDT): Concursus Realis by the Employees of the Pusat Koperasi Veteran Republik Indonesia (Study of Decision No. 231/Pid.B/2021/PN.Gdt) - Samantha Gloria Hoetama; Tawang, Dian Adriawan Daeng (Reformasi Hukum Trisakti, 2025)
The desire to fulfill life's needs can encourage a person to commit acts that violate the law, so nowadays there are many people who commit multiple criminal offenses simultaneously. In Decision No. 231/Pid.B/2021/PN.Gdt. there is a concursus realis, where the defendant committed two criminal acts at once: embezzlement for livelihood and forgery of letters. The identification of the problem in this study is the act of the employee of the Veteran Cooperative Centre of the Republic of Indonesia in Decision No. 231/Pid.B/2021/PN.Gdt. a concursus realis according to the Criminal Code? This research is a normative legal research, descriptive in nature, using secondary data, and analysed qualitatively. The results of the discussion and conclusions show that the employees of the Veterans Cooperative Centre of the Republic of Indonesia did not only commit the crime of embezzlement for livelihood in accordance with Article 374 of the Criminal Code, but also fulfilled the elements of the crime of mail fraud in accordance with Article 263 of the Criminal Code which constitutes concursus realis.